ANALISIS TREND HARGA BAWANG MERAH DI KABUPATEN ALOR - Maure, Gerson Hans (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2023)
Vegetable plants are one of the leading horticultural crops in the agricultural sector in Indonesia which are in great demand by the public because they have high nutritional content. Shallots are one of the leading vegetable commodities that are in great demand by the public as a cooking spice and as medicine. As the population increases and the development of industries that require shallot raw materials, the demand for shallots continues to increase. This research was conducted to determine price trends and forecast the price of shallots in Alor Regency in the future. The data analysis method used in this research is analysis of development trends and trends in onion price movements using the least squares method formula with the help of MS Excel. The research results show that the development of the price of shallots in Alor Regency from January 2020 to December 2022 shows the direction of an increase in prices each month of IDR. 259.59/kg with a determinant coefficient of R2 = 0.1064 or 10.64%. The forecast for the price of shallots in Alor Regency in 2023 is likely to continue to increase slowly. It is hoped that the government can maintain the stability of shallot prices both at the producer and consumer levels, because predictions of shallot prices in the future continue to increase.